Level of exclusive breastfeeding practice in remote and pastoralist community, Aysaita woreda, Afar, Ethiopia - Medhin Tsegaye; Dessalegn Ajema; Solomon Shiferaw; Robel Yirgu (BMC, 2019)
Abstract Background In Afar, a pastoralist and remote area of Ethiopia, one in five children suffers from acute malnutrition. Investigation of the prevalence and associated factors of exclusive breastfeeding may provide insight into the current burden and nature of the problem, and offer help on how to direct prevention strategies. The aim of this study was to measure the prevalence and identify associated factors of exclusive breastfeeding (EBF) practice in Afar, Ethiopia. Methods A community based cross-sectional study was conducted with qualitative inquiry from March to April 2015. Quantitative data were collected from 631 mother-infant pairs residing in Aysaita woreda with a pretested structured questionnaire using the modified expanded program on immunization cluster sampling procedure. Seven clusters were selected using probability proportional to size. The qualitative data were generated through two focus group discussions among purposely selected discussants: one group of eight health professionals and another group of mothers, fathers and traditional birth attendants (n = 10). Bivariate and multivariable analysis was done using binary logistic regression model while thematic framework analysis was employed for the qualitative data. Results The prevalence of EBF under six months of age was 340/618 (55%). Infants whose mothers resided in an urban area [Adjusted Odds Ratio (AOR) 5.7; 95% Confidence Interval (CI) 3.5, 9.2), were knowledgeable about breastfeeding (AOR: 2.3; 95% CI 1.6, 3.5) and delivered at health facilities (AOR: 1.7; 95% CI 1.1, 2.7), were more likely to be exclusively breastfed than the referent group. In addition, mothers had a poor understanding of what constitutes exclusive breastfeeding. Traditional beliefs, myths and misconceptions about EBF and lack of support from husband and family were found to be barriers for proper EBF practice. Conclusions The prevalence of EBF did not meet the World Health Organization recommendations. Factors related to infrastructure, service delivery, health education packages and traditional beliefs were associated with EBF practice.